2016
DOI: 10.1111/mcn.12247
|View full text |Cite
|
Sign up to set email alerts
|

Maternal mental health symptoms are positively related to emotional and restrained eating attitudes in a statewide sample of mothers participating in a supplemental nutrition program for women, infants and young children

Abstract: Postpartum, low-income mothers are at risk for mental health symptoms and obesity, and disordered eating attitudes may be associated with both mental health and obesity in this vulnerable population. The study objective is to determine whether higher levels of mental health symptoms are associated with increased odds of emotional and restrained eating attitudes in this sample of Special Supplemental Nutrition Program for Women, Infants and Children (WIC) participants. Data on 711 mothers of infants <13 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 55 publications
2
15
0
Order By: Relevance
“…The results of this study also call attention to the type of care provided by the mother for her baby, since unhealthy food choices are often made, including when considering the weaning, which corroborates other studies that focus on the influence of food during the mother-child relationship [47,48]. …”
Section: Discussionsupporting
confidence: 86%
“…The results of this study also call attention to the type of care provided by the mother for her baby, since unhealthy food choices are often made, including when considering the weaning, which corroborates other studies that focus on the influence of food during the mother-child relationship [47,48]. …”
Section: Discussionsupporting
confidence: 86%
“…One high‐quality and one fair‐quality prospective cohort study found that disordered eating during the post‐partum period was associated with depressive symptoms (Carter et al, ; Lai et al, ), however, only one study demonstrated direction of association with disordered eating at 4 months post‐partum, predicting depressive symptoms at 14 months post‐partum (Carter et al, ). One high‐quality cross sectional study demonstrated an association between disordered eating during the post‐partum period and depressive symptoms within the year after birth (Emerson et al, ). There was not enough evidence to determine a direction of association.…”
Section: Resultsmentioning
confidence: 99%
“…There was no evidence to support an association between disordered eating and anxiety during the post‐partum period, as one fair‐quality prospective cohort study did not find an association between disordered eating and anxiety during the post‐partum period (Carter et al, ). One high‐quality cross sectional study found that emotional eating, but not restrained eating, was associated with anxiety within the year after birth (Emerson et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…62 In a larger sample of postpartum women who participated in the program (n¼711), anxiety, depression, and perceived stress were strongly associated with emotional eating; depression was associated with dietary restraint. 63 Furthermore, stressful events were linked to emotional eating in qualitative study of low-income overweight/obese mothers. 64 The consistency of findings in these studies suggests that interventions aimed at improving dietary intake should consider stress and eating behaviors.…”
Section: Evidence Of a Relationship Between Stress And Dietmentioning
confidence: 99%